PERSONAL EXPOSURE OF AIRLINE FLIGHT ATTENDANTS TO ENVIRONMENTAL TOBACCO SMOKE - EATOUGH,DJ; HUNTER,DR (Tufts Archival Research Center, 2007)
Research proposal for a study on the exposure of flight attendants to environmental tobacco smoke (ETS) conducted by Hart Scientific for R.J. Reynolds. Proposes to measure exposure by using personal exposure sampling devices and portable briefcase sampling systems.